THE DYNAMICS OF LAW ENFORCEMENT IN REGIONAL HEAD ELECTIONS DURING COVID-19 PANDEMIC - Mirza Nasution; Muhammad Yusrizal Adi Syaputra (Jurnal Pembaharuan Hukum, 2021)
The state is a social entity that consists of areas that have almost similar historical-cultural backgrounds. These areas have administrative divisions that are hierarchical in nature, where the division aims to accelerate the development and improvement of the area and the people in it. The research method used in this research is normative legal research method. The normative legal research method is a research method that looks for facts through the variables derived from the laws and regulations that are examined on their implementation and their effectiveness and shortcomings so that improvements and improvements can be made to these laws and regulations. Regional head elections are an inseparable part of a country that adheres to the principles of democracy and is even part of the characteristics of a democratic country.